Treatment with immune checkpoint inhibitors after EGFR‐TKIs in EGFR‐mutated lung cancer. Issue 3 (13th December 2021) - Ito, Takashi; Nagashima, Hiromi; Akiyama, Masachika; Utsumi, Yu; Sato, Hideomi; Chiba, Shinji; Sugai, Mayu; Ube, Kenji; Mori, Yoshiaki; Watanabe, Kana; Fukuhara, Tatsuro; Maemondo, Makoto
Abstract: Background: Epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKIs) have become the gold standard for EGFR ‐mutated non‐small cell lung cancer (NSCLC) treatment. Immune checkpoint inhibitors (ICIs) have been developed for the treatment of several malignancies, including lung cancer. However, it is known that ICIs have poorer efficacy in EGFR ‐mutated NSCLC. Methods: We collected data for patients with EGFR ‐mutated NSCLC receiving monotherapy with ICIs after EGFR‐TKIs between December 2015 and March 2020 in three institutions, and retrospectively analyzed the association between patient characteristics and efficacy of ICIs. Results: A total of 25 patients were included in this study. We defined responders as patients undergoing 90 days or longer of ICI treatment. Comparing characteristics between responders and non‐responders, more tumors with L858R EGFR mutation were observed in responders than in non‐responders (L858R: 66.7% and 25.0%, respectively, p < 0.05). There was no difference in incidence of T790M resistance mutation before ICI treatment. The PD‐L1 positive rate was slightly higher in responders but not statistically significant (22.2% and 12.5%, respectively). Median duration of EGFR‐TKI pretreatment was shorter in ICI responders compared with nonresponders (13.3 and 19.9 months, respectively). The survival of patients with L858R tumors was significantly longer than that of patients with exon 19 deletion (HR: 0.35, 95% CI: 0.13–0.93, p = 0.026). Conclusions: ICI treatment tends to have better efficacy in patients with L858R‐mutated tumors. This study suggests that patients with L858R‐mutated NSCLC are candidates for ICI treatment after EGFR‐TKI treatment. Abstract : Efficacy of ICI in a part of patients with EGFR ‐mutated NSCLC was observed. ICI treatments in tumors with L858R mutation achieved a better response than exon 19 deletion. This study suggests that patients with L858R‐mutated NSCLC are candidates for ICI treatment after EGFR‐TKI treatment.